Structures of Influence A Comparative Approach to August Strindberg - Johns Blackwell, Marilyn (UNC Studies in the Germanic Languages and Literatures, 1981)
This collection of essays featuring contributions from eminent Swedish and American Strindberg scholars addresses the question of how Strindberg's art collides and colludes, ideologically and aesthetically, with the literary "doyens" of the nineteenth and twentieth centuries in both the Scandinavian and the larger Western cultural context.